A Five‐Coordinate Compound with Inverted Ligand Field: An Unprecedented Geometry for Silver(III). Issue 51 (9th November 2021) - Joven‐Sancho, Daniel; Baya, Miguel; Martín, Antonio; Orduna, Jesús; Menjón, Babil
Abstract: By using suitable synthetic procedures, we have first isolated the square‐planar organosilver(III) compounds [PPh4 ][ trans ‐(CF3 )2 AgX2 ] [X=Cl (1 a ), Br (2 a )]. The geometry and stereochemistry of the chloro‐derivative 1 a have been unambiguously established by single‐crystal X‐ray diffraction (SC‐XRD) methods. Following our calculations on the relative stability of the cis ‐/ trans ‐[(CF3 )2 AgX2 ] − couples (X=F, Cl, Br, I), the experimentally obtained compounds 1 a and 2 a appear to be kinetically favored stereoisomers. They display some tendency to associate an additional X − ligand affording rare five‐coordinate Ag III species [(CF3 )2 AgX3 ] 2− . Interestingly, compound [PPh4 ]2 [(CF3 )2 AgBr3 ] (3 ) has been identified by SC‐XRD methods as the first Ag III derivative with trigonal symmetry in general and trigonal bipyramidal geometry in particular. This unusual five‐coordinate species also exhibits inverted ligand field. Abstract : The square‐planar organosilver(III) complex [ trans ‐(CF3 )2 AgBr2 ] − (16 electron) undergoes a marked stereochemical change upon coordination of an additional Br − ligand. The resulting five‐coordinate [(CF3 )2 AgBr3 ] 2− complex (18 electron) exhibits trigonal bipyramidal geometry, which is unprecedented for Ag III . This five‐coordinate compound also exhibits inverted ligand field.